Homeric motivation and modern narratology: the case of Penelope - Grethlein, Jonas (The Cambridge classical journal, 2018)
Forged mostly in readings of the modern novel, the tools of narratology have allowed us to detect many features that ancient literature shares with modern texts. At the same time, they have detracted from crucial differences between ancient and modern narratives. This article argues that, while being at the origin of the classical western plot, the Odyssey also features a narrative logic that differs significantly from what the modern novel has taught us to expect. It focuses on the case of Penelope. Various theories have been advanced to explain Penelope's intervention in books 18 and 19. The difficulties that modern scholars have had with Penelope, it is suggested, are due to a special kind of motivation which is also prominent in medieval narrative.